(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Public international law is no longer a traditional law. Its function is not only to regulate international relations among its people in the international community, but it also has new topics to deal with by its legal rules. New scourges have emerged at the international level in the context of globalization, which has taken international law out of its traditional garb in an effort to combat such phenomena. While the specific legal nature of international crime differs from domestic crime, both in terms of the source of the offense and the elements and elements underlying it, it differs from that of transnational organized crime, which requires careful examination of the concept of international crime and transnational organized crime the interval between them. لم يعد القانون الدولي العام قانوناً تقليدياً، وظيفته مقتصرة على تنظيم العلاقات الدولية بين أشخاصه في المجتمع الدولي فقط، بل أصبح له مواضيع جديدة يعالجها ويتناولها بقواعده القانونية. فقد ظهرت آفات جديدة على الصعيد الدولي في ظل العولمة، أخرجت القانون الدولي من ثوبه التقليدي، سعياً لمكافحة تلك الظواهر، وتعدّ الجريمة المنظمة عبر الوطنية، بصورها المتنامية، من أبرز تلك الظواهر التي شغلت الفكر الجزائي في الأونة الأخيرة. وإذا كانت الطبيعة القانونية الخاصة بالجريمة الدولية تختلف عن الجريمة الداخلية، سواء من حيث مصدر التجريم أو الأركان والعناصر التي تقوم عليها، إلا أن ذلك يختلف عنه في الجريمة المنظمة عبر الوطنية، بسبب طبيعتها المتداخلة، الأمر الذي يتطلب البحث الدقيق في مفهوم الجريمة الدولية والجريمة المنظمة عبر الوطنية لمعرفة الحد الفاصل بينهما.